The prototype Schwarzschild Couder Telescope: A Medium-Sized Telescope for the Cherenkov Telescope Array - Romana Pantaleo Francesca (EPJ Web of Conferences)
The Schwarzschild-Couder Telescope (SCT) is a dual-mirror telescope designed for the Cherenkov Telescope Array Observatory (CTAO) to observe very-high-energy gamma rays (20 GeV to 300 TeV). It features a dualmirror system and a high-resolution camera with an 8° field of view (FoV) for enhanced angular resolution and background rejection. A prototype (pSCT) is operational at the Fred Lawrence Whipple Observatory (FLWO) in Arizona, with a 2.7° FoV SiPM array. The pSCT recently detected the Crab Nebula with 8.6 standard deviations of significance. The focal plane is currently being upgraded to improve sensors and expand the FoV from 2.7° to 8°. An overview of the pSCT project, its results, and the camera upgrade will be presented.